Insecticidal and Repellent Activity of Plant Powders on the Weevil (Sitophilus zeamais) in Stored Corn Grains in a Rural Community of Oaxaca, Mexico - Citlaly Peña-Flores; Arturo Zapién-Martínez; Gabriel Sánchez-Cruz; Leobardo Reyes-Velasco; Aristeo Segura-Salvador; Jaime Vargas-Arzola; Luis Alberto Hernández-Osorio; Honorio Torres-Aguilar; Héctor Ulises Bernardino-Hernández (Insects)
The bioinsecticidal and repellent effect of four plant powders (Chenopodium ambrosioides, Piper auritum, Laurus nobilis, and Origanum vulgare) was evaluated in the control of Sitophilus zeamais adults in corn grains stored in the rural community of Santa María Zacatepec, Oaxaca, Mexico. Using completely randomized experimental designs, concentrations of 1%, 2%, and 3% by mass of corn grains infested with adults of S. zeamais were tested; the controls were corn without powder and aluminum phosphide. The analysis was performed using ANOVA with Tukey’s post hoc and Student’s t-tests. The highest mortality (>80%) and repellent effect (Repellent Index < 0.3) that were statistically significant were obtained with C. ambrosioides and P. auritum at 3%. Both plant species have the potential for weevil control in stored corn and represent a friendly alternative for the environment and public health in the rural community where the study was conducted.